(untitled) (Jurnal EurekaMatika, 2023)
ABSTRACT This study is about analysis by creating a Nelson-Aalen curve and determining differences in the curve between categories of each risk factor for Type II Diabetes Mellitus. The analysis method used is the Nelson-Aalen method which is used to create a curve by calculating the cumulative hazard value first and then followed by calculating survival odds, and the Weighted Log Rank Test is used to determine the difference in the curve. The data used was the medical record data of inpatients with Type II Diabetes Mellitus at the Sayang Public Hospital of Cianjur Regency. The result obtained is that the Nelson-Aalen curve shows decreased characteristics, namely the longer the patient is treated, the patient’s chances of recovery will be smaller. In other words, the patient’s chances of returning home in a state of recovery will be even greater. Furthermore, the test results showed that there was no difference in the case of survival in the factors of age, hypertension, current blood sugar levels, and diabetic legs, while gender factors and balanced diet patterns showed a difference in the chance of survival, which means that both factors affect the chances of survival of Type II Diabetes Mellitus patients at the Sayang Public Hospital of Cianjur Regency. ABSTRAK Pada penelitian ini disajikan analisa ketahanan hidup dengan membuat kurva Nelson-Aalen dan menentukan perbedaan kurva antar kategori dari setiap faktor risiko Diabetes Mellitus Tipe II. Metode analisis yang digunakan adalah metode Nelson-Aalen yang digunakan untuk membuat kurva ketahanan hidup dengan menghitung nilai hazard kumulatif terlebih dahulu lalu dilanjutkan dengan menghitung peluang ketahanan hidup. Weighted Log Rank Test digunakan untuk menentukan perbedaan kurva. Data yang digunakan adalah data rekam medis pasien rawat inap penderita Diabetes Mellitus Tipe II di RSUD Sayang Cianjur. Diperoleh hasil bahwa kurva Nelson-Aalen menunjukkan karakteristik yang menurun, yaitu semakin lama pasien dirawat maka peluang pasien untuk belum mengalami kesembuhan akan semakin kecil. Dengan kata lain, peluang pasien untuk pulang dalam keadaan telah mengalami kesembuhan akan semakin besar. Selanjutnya, hasil pengujian menunjukkan bahwa tidak terdapat perbedaan peluang ketahanan hidup pada faktor usia, hipertensi, kadar gula darah sewaktu, dan kaki diabetik, sedangkan faktor jenis kelamin dan pola diet seimbang menunjukkan adanya perbedaan peluang ketahanan hidup, yang artinya kedua faktor tersebut memengaruhi peluang ketahanan hidup pasien Diabetes Mellitus Tipe II di RSUD Sayang Kabupaten Cianjur.